Macrotranscriptomics analysis for decoding the role of Klebsiella variicola H8 in aroma compound biosynthesis during fermentation of reconstituted tobacco leaf concentrate - Feng, Yingjie; Qi, Wenyuan; Yang, Jinchu; Liu, Wenzhao; Yang, Zongcan; Wang, Ke; Mao, Duobin; Huang, Shen; Zhang, Tingting (Frontiers in Bioengineering and Biotechnology, 2025)
Microbial fermentation shapes the reconstituted tobacco leaf concentrate’s (RTLC) chemical composition and sensory quality. This study employed macrotranscriptomic analysis to investigate how the aroma-enhancing bacterium Klebsiella variicola H8 modulates RTLC fermentation. High-throughput second-generation RNA sequencing revealed that the transcript abundance of K. variicola H8 increased from 5.92% at the start of fermentation to 14.78% at 16 h, accompanied by the enrichment of other key genera such as Lactobacillus and Citrobacter. Differential gene expression analysis showed that K. variicola H8 transcription correlated strongly (R2 = 0.85) with water-soluble sugar degradation, while nitrogen and potassium correlations were weaker (R2 = 0.47 and 0.41, respectively). Notably, the upregulation of glycoside hydrolases-particularly GH78, GH13_25, GH31, and GH28-was associated with the release of key non-volatile aroma-enhancing compounds (NAECs), such as β-damascenone (13.24 μg/g), phenylethanol (7.12 μg/g), solanone (5.89 μg/g), dihydrokiwi lactone (6.03 μg/g), and benzyl alcohol (5.15 μg/g). Furthermore, expression levels of apoptosis-related genes increased at 36 h, coinciding with a decline in sensory quality and aroma compound accumulation. These findings reveal the dynamic microbial and enzymatic processes underpinning NAEC production and provide a mechanistic basis for optimizing microbial fermentation in tobacco processing.